172k views
0 votes
-3/4(x+2)=6

What is the answer please explain how u got it​

2 Answers

6 votes
The answer is: x = -10; Step 1- Combine multiplied terms into a single fraction: -3(x+2)/4 = 6. Step 2- Distribute: -3x - 6/4 = 6. Step 3- Multiply all terms by the same value to eliminate fraction denominators: 4 x -3x - 6/4 = 6 x 4. Step 4- Cancel multiplied terms that are in the denominator: -3x - 6 = 4 x 6. Step 5- Multiply the numbers: -3x - 6 = 24. Step 6- Add 6 to both sides of the equation: -3x - 6 + 6 = 24 + 6. Step 7- Simplify: -3x = 30. Step 8- Divide both sides of the equation by the same term: -3x/-3 = 30/-3. Step 9- Simplify: x = -10.
User Masuk Helal Anik
by
6.2k points
1 vote

Explanation:

1.) distribute (-3/(4x+8)=6)

2.) move 8 (-3/4x=-2)

3.) multiply by 4x (-3= -8x)

4.) divide by -8 (x=2.6)

:)

User Sajid Ali
by
6.4k points